الثقافة المدرسية وترسيخ قيم المواطنة لدى الناشئة - د.علي شريف, حورية; سعاد, د.بن ققة (دفـاتر المـــــــــــخبـر, 2018)
الملخص تعد المواطنة في حقيقتها وعي الشخصلمجموعةمن الحقوق والواجبات والعمل بها، باعتباره عضوا في مجتمع يمتاز بحركية وتحولات، وفي ظل هذه الحركية تتكون تلك الحقوق والواجبات، وتخلق الحاجات والمسئوليات فيتولد موروث مشترك من المبادئ والقيم والعادات والسلوكات. ولما كانت التربية المرتكز الاساسي في أعداد الناشئة وتكوينهم، وتحقيق ذلك، كان لزاما على المدرسة غرس وترسيخ قيم ومعتقدات المجتمع، لدى التلاميذ. وإن هذا العمل يتوقف بدرجة كبيرة على ثقافة المدرسة، وانطلاقا من هذا الطرح تحاول هذه الورقة البحثية الكشف عن الآليات التي تجعل من الثقافة المدرسية فعالة في ترسيخ قيم المواطنة لدى الناشئة. Abstract: Citizenship is in fact a person's awareness of a set of rights and duties and work as a member of a society characterized by mobility and transformations. In this dynamic, these rights and duties are formed, creating the needs and responsibilities, creating a common heritage of principles, values, customs and behaviors. As education is the main foundation in the preparation and composition of young people, and to achieve this, it was necessary for the school to instill and consolidate the values ​​and beliefs of the community, the pupils. This work depends largely on the culture of the school. Based on this thesis, this paper attempts to uncover the mechanisms that make the school culture effective in establishing the values ​​of citizenship among the youth.